Chemical Bath Deposition of ZnSe Thin Films: Investigations of the Growth Conditions - Ho, Soon Min (Sciencedomain International HR, 2016)
The main objective of this work was to deposit zinc selenide thin films onto glass substrate by using chemical bath deposition technique. ZnSe films could be used in solar cell applications. The chemical bath deposition method was chosen due to have many advantages if compared to other deposition techniques. Zinc acetate and sodium selenosulphate were used to provide the zinc and selenide ions, respectively. In this work, energy dispersive X-ray analysis (EDAX) and UV-Visible spectrophotometer technique were applied in order to study the properties of obtained ZnSe films which prepared under various pH values ranged from 10.2 to 11.2. The zinc rich content could be observed at these pH values as indicated in EDX results. The band gap was determined by using absorption spectra. The band gap was increased from 2.7 to 2.85 eV as the pH was increased from 10.2 to 11.2.